The Possibility of Hope: Introspective and Aesthetical Analyses - Lee, Sang (Pastoral psychology, 2015)
I discuss hope as a generator of resilience, the relationship of faith and hope, hope as the experience of being at home, hope as self-contentment, and hope as traveling through life. I illustrate the capacity to hope in the midst of despair through paintings by Paul Gauguin and poetry by Shibata Toyo, and I use the parable of the Good Samaritan to illustrate what I mean by traveling through life in an unhurried, self-contented way. I use D. W. Winnicott's writings to support the association of faith and hope, Freud's essay on the uncanny to develop hope as the sense of being at home, and Erik H. Erikson's writings on trust in support of the view that hope is possible in the very midst of despair.